#TITLE_ALTERNATIVE# - PURNAMA SIDIQ (NIM 25106008), TEGUH
Interferometry Synthetic Aperture Radar (InSAR) technology was developed long ago outside Indonesia. The use of this technology in geodesy has been developed well because its capability to build DEM and very accurate to detect small movement of the earth (deformation). This thesis study about the use of InSAR for deformation observation in Indonesia that have not been done very often in Indonesia. SAR data used on this thesis include three kind of SAR satellites, they are ALOS PALSAR data, ENVISAT data, and ERS-1/2 data. Two pass differential Interferometry method is used to extract the deformation using Gamma Software. DEM from SRTM data are used as auxiliary data on the processing. There are five areas studied on this thesis, ther are Bandung area, Semarang City, Medan City, Batur Volcano, and Ibu Volcano. Each area has thir own characteristic, so each area could give unique lesson learn of InSAR data processing. From the result of data processing we can see that the three big cities that was studied on this thesis are having subsidence. Bandung area has different type of subsidence compared to Somarang city. In Bandung, the deformation pattern is more local to what happen in Semarang city. And we can also see that the subsidence happened in Medan city is more like Bandung subsidence. The deformation in Batur volcano is relativly small, and also support the earlier conclusion (Ony, 2008), but the data was processed using different algorithm. The same patern of deformation is also shown in Ibu volcano. Unfortunately, the coherence in both volcano data processing is not very good, so the value of deformation is less significant. The less of coherence in all data processing on this study are more caused by heavy tree canopy that is occure in almost all Indonesia region. In Bandung area, Semarang City, and Medan City, water cover some part of the area so the coherence drop significantly.